Aster Retail UAE (a) : connecting employees, customers, and business results - Varkkey, Biju; Trivedi, Bhumi (London : Indian Institute of Management, Ahmedabad, 2020)
Aster Retail (AR) is the retail pharmacy division of the Aster Dr. Moopen's Healthcare (ADMH) Group. The group delivers healthcare services across the Middle East, India, and the Far East, with a portfolio of hospitals, clinics, diagnostic centres, and retail pharmacies. AR, under the leadership of Chief Executive Officer (CEO) Jobilal Vavachan, is well known for its people-centric approach, unique culture, and innovative human resource (HR) practices. AR has won multiple awards for HR practices, service quality, and business performance. In a recent corporate restructuring (2018), "Aster Primary Care" was carved out by combining the group's Clinics and Retail businesses. This case discusses the evolution of AR's HR journey and the challenges associated with integrating culturally diverse businesses without compromising the values of ADMH and its promise, "We'll Treat You Well."
Description based on XML content.
Keywords: elektronické knihy; electronic books; Pharmaceutical industry -- Management; Personnel management